Development of a Conceptual Understanding Procedures (CUPs)-Based Learning Module to Improve Problem-Solving Skills in Fourth-Grade Elementary School Mathematics Learning - Donna Boedi Maritasari; Doni Septu Marsha Ibrahim; Asara Putri Nadiwa (Lembaga Bale Literasi, 2026)
This research aims to develop a Cups (Conceptual Understanding Procedures) learning module to improve fourth-grade problem-solving skills in elementary schools. The research method used in this study is ADDIE, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects were fourth-grade students of SDN 1 Kembang Kuning, Sikur District. The research instruments consisted of expert validation sheets (media and materials) and student response questionnaires. The validation results indicate that the learning module is categorized as “valid.” Media experts gave a score of 61 with an average of 4.0, and material experts gave a score of 71 with an average of 4.7. Student responses also showed positive results, achieving a score of 672. These results demonstrate that the learning module is not only valid and feasible to use, but also effective in increasing interest in problem-solving skills in fourth-grade elementary school students while providing a more meaningful learning experience. Therefore, it can be concluded that this product has the potential to be an alternative, innovative learning medium to improve the quality of learning in elementary schools.